Sputum containing zinc enhances carbapenem resistance, biofilm formation and virulence of Pseudomonas aeruginosa - Marguerettaz, Mélanie; Dieppois, Guennaëlle; Que, Yok Ai; Ducret, Véréna; Zuchuat, Sandrine; Perron, Karl (Microbial pathogenesis, 2014)
Pseudomonas aeruginosa chronic lung infections are the leading cause of mortality in cystic fibrosis patients, a serious problem which is notably due to the numerous P. aeruginosa virulence factors, to its ability to form biofilms and to resist the effects of most antibiotics. Production of virulence factors and biofilm formation by P. aeruginosa is highly coordinated through complex regulatory systems. We recently found that CzcRS, the zinc and cadmium-specific two-component system is not only involved in metal resistance, but also in virulence and carbapenem antibiotic resistance in P. aeruginosa. Interestingly, zinc has been shown to be enriched in the lung secretions of cystic fibrosis patients. In this study, we investigated whether zinc might favor P. aeruginosa pathogenicity using an artificial sputum medium to mimic the cystic fibrosis lung environment. Our results show that zinc supplementation triggers a dual P. aeruginosa response: (i) it exacerbates pathogenicity by a CzcRS two-component system-dependent mechanism and (ii) it stimulates biofilm formation by a CzcRS-independent mechanism. Furthermore, P. aeruginosa cells embedded in these biofilms exhibited increased resistance to carbapenems. We identified a novel Zn-sensitive regulatory circuit controlling the expression of the OprD porin and modifying the carbapenem resistance profile. Altogether our data demonstrated that zinc levels in the sputum of cystic fibrosis patients might aggravate P. aeruginosa infection. Targeting zinc levels in sputum would be a valuable strategy to curb the increasing burden of P. aeruginosa infections in cystic fibrosis patients. •Sputum of cystic fibrosis patients contains excess of zinc.•We use an artificial sputum medium to observe the effect of zinc on Pseudomonas aeruginosa.•Zinc exposure activates the pathogenicity, carbapenem resistance and biofilm formation of P. aeruginosa.•Zinc represses the expression of the OprD porin via a yet unknown mechanism.•Our data show that zinc levels in sputum of cystic fibrosis patients might aggravate P. aeruginosa infection.